Hegemonic and shamed masculinities: Implications of traumatic historical impacts on black men in a post democratic South Africa - Govender, Kaymarlin; Cartwright, Duncan James (PINS-Psychology in Society, 2022)
The landscape of post-Apartheid South Africa is characterised by high levels of male perpetrated violence against women, children and other men with blame often attributed to victims rather than perpetrators (Hayes & Abbot, 2016). The aberrant behaviours and attitudes of men (also referred to as toxic masculinity) has been central to the notion of a so-called contemporary ‘crisis in masculinity’ with violence and risk taking behaviours (alcohol, substance abuse, sexual risk taking) embedded in male culture. While previous explanations of the ‘modern day crisis’ among men can be largely attributed to South Africa’s history of violent and traumatic struggles of domination over place, ideology and bodies, there is a paucity of work theorising this crisis from a socio-historical and psychodynamic trauma paradigm. In this vein, this paper delves into key periods of our history (referred to as ‘chosen traumas’) that have had persistent disruptive influences on particularly, black masculinity, which have collectively contributed to the modern day crisis. Our argument relies on the idea that unresolved historical traumas have a transgenerational ‘haunting’ effect on contemporary identities (Gordon, 1997; Layton, 2019). Focusing on black men who were subjected to a violent and repressive past, we have argued that ghosts of the pre-Apartheid to post-Apartheid modern day South Africa continue to have cumulative impacts on the black male psyche. It is suggested that these past traumas, together with contemporary representations of black masculinity, have led to a deep sense of unresolved shame, the dynamics of which we have attempted to illuminate using psychodynamic and masculinity theory. The paper concludes with some recommendations on dealing with unresolved traumas and violence.